2020
DOI: 10.1371/journal.pone.0230874
|View full text |Cite
|
Sign up to set email alerts
|

A MAGEL2-deubiquitinase complex modulates the ubiquitination of circadian rhythm protein CRY1

Abstract: MAGEL2 encodes the L2 member of the MAGE (melanoma antigen) protein family. Protein truncating mutations in MAGEL2 cause Schaaf-Yang syndrome, and MAGEL2 is one of a small set of genes deleted in Prader-Willi syndrome. Excessive daytime sleepiness, nighttime or early morning waking, and narcoleptic symptoms are seen in people with Prader-Willi syndrome and Schaaf-Yang syndrome, while mice carrying a gene-targeted Magel2 deletion have disrupted circadian rhythms. These phenotypes suggest that MAGEL2 is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…After data processing, 44 CtermMAGEL2-proximal proteins were identified ( Table S2 ). One protein, USP7, had been previously identified as a CtermMAGEL2 interactor by tandem affinity purification and coimmunoprecipitation, while the other proteins were not previously associated with MAGEL2 ( 8 , 9 ). While we consider these to be potential C-terminal interacting proteins, it is also possible that the N-terminal protein of MAGEL2 could alter the conformation of the C-terminal portion of the protein and influence recruitment of its binding partners.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After data processing, 44 CtermMAGEL2-proximal proteins were identified ( Table S2 ). One protein, USP7, had been previously identified as a CtermMAGEL2 interactor by tandem affinity purification and coimmunoprecipitation, while the other proteins were not previously associated with MAGEL2 ( 8 , 9 ). While we consider these to be potential C-terminal interacting proteins, it is also possible that the N-terminal protein of MAGEL2 could alter the conformation of the C-terminal portion of the protein and influence recruitment of its binding partners.…”
Section: Resultsmentioning
confidence: 99%
“…MAGE proteins regulate protein ubiquitination, through interactions between the MHD and variable domains of E3 ubiquitin ligases and deubiquitinases, to form MAGE-RING E3 ligase complexes that serve as multifunctional hubs for the modification of key substrates in the cell ( 2 , 3 , 4 ). MAGEL2 regulates the vesicular and endosomal trafficking of membrane-bound receptors and also regulates the stability of proteins important for nuclear-cytoplasmic trafficking, cilia, and other cellular activities ( 5 , 6 , 7 , 8 , 9 , 10 ). However, functional studies have assessed only a truncated version of the MAGEL2 protein that contains the C-terminally located MHD but not the N-terminal portion of the protein ( 6 , 7 , 8 , 11 , 12 , 13 , 14 , 15 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, it was shown that MAGEL2, a protein known to interact with ubiquitin ligases and DUBs, interacts with USP7 and prevents its binding to CRY proteins. Furthermore, MAGEL2 over‐expression led to a reduction in CRY levels, showing that USP7 is required for the deubiquitination and stability of CRY proteins (Carias et al., 2020). The circadian expression of MAGEL2 suggests that the phased activity of USP7 might be regulated by the presence of MAGEL2.…”
Section: Ubiquitination and Deubiquitination In The Clock Of Mammalsmentioning
confidence: 99%
“…However, SYS patients and mouse models with MAGEL2 mutations show a lower prevalence of overeating and obesity. Instead, it was determined that MAGEL2 functions as a ubiquitin transporter that localizes in SCN neurons and acts as a direct regulator of circadian clock proteins through ubiquitination ( Mercer et al, 2009 ; Tacer and Potts, 2017 ; Vanessa Carias et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%